Fractionation of proteins from the venom of snake Ophiophagus hannah in Vietnam and their effects on adipogenesis in 3T3-L1 cells - Nhung, Nguyễn Thị Tuyết; Hiền, Vũ Thị; Hoa, Phạm Thị; Thu, Hà Thị; Hoa, Nguyễn Thị; Linh, Mai Thùy; Triều, Nguyễn Hải; Lành, Phạm Thị; Kháng, Đinh Duy; Quyền, Đồng Văn (Vietnam Journal of Biotechnology, 2016)
Snake venom is a mixture of different components with a great variety of biological effects. Some components in snake venom have been found to act specifically and potently on their targets. Unlike the venom of Naja naja, Echis carinatus, Vipera russellii which are widely used, there is little attention has been given to Ophiophagus hannah even this is the largest venomous snake in the world. In this study, using O. hannah venom collected at Dong Tam Snake Farm in Tien Giang Province, we have collected 4 protein fractions using membrane cut-off centrifugal filters, ie., YM100, YM50, YM 30, YM10 and YM3. Of the 4 fractions including (1) proteins from 3 kDa to smaller than 10 kDa, (2) proteins from 10 kDa to smaller than 30 kDa, (3) proteins from 30 kDa to smaller than 50 kDa and (4) proteins from 50 kDa to smaller 100 kDa, fraction 4 accounted for the highest proportion whereas fraction 3 is the lowest proportion. Following the demonstration of many medicinal uses of snake venom, potential effect of fraction 1 on obesity was examined. Although multiple molecular processes are involved in the progression of the disease, obesity can accompany increase in adipocyte size as a consequence of accumulation of lipid droplets within the fat cell, as well as increased number of adipocytes resulting from differentiation of precursor cells. In our study, two different concentrations of 1 μg/mL and 10 μg/mL proteins in fraction 1 were investigated for effectiveness on the 3T3-L1 cells differentiation and adipogenesis. The obtained results showed that, at the concentration of 10 μg/mL, this fraction inhibited the adipogenesis which have been shown by accumulation of lipid droplets within the 3T3-L1 cells. Besides, at a concentration of 10 μg/mL, fraction 1 had no cytotoxic effect on cell viability of 3T3-L1 cells